Inclusive Education as an Alternative to Improve Access to Education for Children with Disabilities in Society - Ompusunggu, Alex R I; Achidiani, Yani; Permata Nastia, Gina Indah (Indonesian Journal Publisher, 2025)
Inclusive education is a strategic approach to ensure equal access to education for children with disabilities while reducing the social discrimination they face. This article employs a literature study method to analyze the role of inclusive education in improving access to education in society. The findings indicate that inclusive education contributes to strengthening social participation, reducing stigma, and creating a supportive learning environment for all children. However, challenges such as limited facilities and lack of teacher training remain significant barriers. This article emphasizes the importance of collaboration between the government, schools, and communities in supporting the effective implementation of inclusive education. Inclusive education is a concrete step toward equality and justice in the education system.